The Importance of Interior Design Perception on Michelin Restaurants - Aytar Sever, ildem (Journal of Interior Design and Academy, 2024)
The aim of this study is to examine relationship between social behavior patterns and spatial fiction. It is generally about examining the relationship between space and behavior through restaurants, which are a specific physical location. Especially design typologies of Michelin restaurants examined; spatial arrangement and spatial fiction of Michelin restaurants selected in Turkey revealed. By identifying behavioral patterns within Michelin restaurants, some inferences about the relationship between physical space and behavior attempted. Although there are many criteria for restaurants classification, especially Michelin restaurants that are recognized worldwide included. Examples of Michelin star restaurants in Istanbul, which has a fascinating history with its unique location connecting two continents that have accompanied many cultures, given and design criteria of these places examined. Literature studies have been carried out on Michelin Guide, which has a significant impact in gastronomy world. Following the literature review, Michelin star restaurants discussed and evaluated for architectural design.